Diets Containing Egg or Whey Protein and Inulin Fiber Improve Energy Balance and Modulate Gut Microbiota in Exercising Obese Rats. Issue 7 (11th February 2022) - Avirineni, Bharath S.; Singh, Arashdeep; Zapata, Rizaldy C.; Stevens, Richard D.; Phillips, Caleb D.; Chelikani, Prasanth K.
Abstract : Scope: Dietary protein, prebiotic fiber, and exercise individually have been shown to aid in weight loss; however less is known of their combined effects on energy balance. The effects of diets high in protein and fiber, with exercise, on energy balance, hormones, and gut microbiota, were determined. Methods and Results: Obese male rats were fed high‐fat diets with high protein and fiber contents from egg protein and cellulose, egg protein and inulin, whey protein and cellulose, or whey protein and inulin, together with treadmill exercise. We found that inulin enriched diets decreased energy intake and respiratory quotient (RQ), increased energy expenditure (EE), and upregulated transcripts for cholecystokinin (CCK), peptide YY, and proglucagon in distal gut. Notably, CCK1‐receptor blockade attenuated the hypophagic effects of diets and in particular whey‐inulin diet, and β‐adrenergic blockade reduced EE across all diets. Egg‐cellulose, egg‐inulin, and whey‐inulin diets decreased weight gain, adiposity, and hepatic lipidosis; decreased lipogenic transcripts, improved glycemic control, and upregulated hepatic glucose metabolism transcripts; and decreased plasma insulin and leptin. Importantly, diet was linked to altered gut microbial composition and plasma metabolomics, and a subset of predicted metagenome pathways and plasma metabolites significantly correlated, with plasma butyric acid the most strongly associated to metagenome function. Conclusion: Combination of dietary egg or whey protein with inulin and exercise improved energy balance, glucose metabolism, upregulated anorectic hormones, and selectively modulated gut microbiota and plasma metabolites. Abstract : High protein diets containing egg or whey protein, together with inulin fiber and exercise, improved energy balance in obese rats by decreasing food intake, enhancing energy expenditure, decreasing fat mass, improving glycemic control, and by modulating metabolic hormones, gut microbiota composition and function, and select metabolites in blood circulation. Interestingly, these diets promoted satiety partly through the gut hormone cholecystokinin.